Perlindungan Hukum bagi Konsumen terhadap Perubahan Bentuk Uang Kembalian ke dalam Bentuk Donasi oleh Pelaku Usaha Alfamart - Alhijrah, Wulan Fadillah (Proceedings Series on Social Sciences & Humanities, 2024)
This writing aims to examine the accountability and legal protection provided by businesses to consumers regarding the conversion of change into donations at Alfamart. This article has two main objectives:1. To analyze the practice of converting consumer change into donations in transactions at Alfamart. 2. To examine the legal protection for consumers regarding the conversion of change into donations according to Law Number 8 of 1999. The research method used in this article is normative research. Normative research is applied as the primary approach to explore legal aspects based on issues reviewed from the perspective of several relevant laws. This approach is expected to encourage sustainable economic growth without harming consumers or users of goods and services. The existence of the Consumer Protection Law is considered sufficiently representative to protect consumers, as long as it is well understood and implemented by businesses and consumers.The enactment of this law provides hope for the Indonesian public to obtain protection against losses incurred from transactions involving goods and services. The Consumer Protection Law ensures legal certainty for consumers, as outlined in Article 3 of Law Number 8 of 1999 on Consumer Protection, which details the objectives of consumer protection.